Effects of seven plant essential oils on mortalities of chicken lice (Lipeurus caponis l.) adult - Pumnuan, Jarongsak; Insung, Ammorn; Klompanya, Ampon (My University, 2020)
Chicken lice (Lipeurus caponis L.) are external parasite of chicken and farmers often use malathion and carbaryl insecticides to control this parasite. However, the use of chemical insecticides may result in direct toxicity to chicken or contamination in chicken meats. Thus, this study investigated the effect of seven plant essential oils (EOs) against adult chicken lice. Contact bioassay was performed by laying 10 adult chicken lice on treated filter paper added with EOs at concentrations of 0 (95% ethanol as a control), 0.079, 0.157, 0.236 and 0.314 μl·cm-2. Mortality percentages were observed at 3, 6 and 12 h intervals after the treatments. Clove, cinnamon, turmeric and star anise EOs were able to eliminate the lice completely (100% mortalities) at 12 h exposure which were higher than lemon grass, citronella grass and piper EOs. Clove EO was the most effective oil with LC50 of 0.132, 0.085 and 0.039 μl·cm-2 at 3, 6 and 12 h, respectively. Furthermore, clove EO at the 0.157 μl·cm-2 showed the highest mortalities with LT50 at 1.438 h. Our study suggests that clove EO could be used as an alternative medicinal insecticide to control chicken lice in farms.
Keywords: Chicken lice; Cinnamon; Clove; Contact method; Insecticide; Star anise